A literatura popular no processo de letramento de jovens e adultos em Alagoa Grande - Macêdo, Wilma Virgínia Carvalho de (2018)
This research aims to verify the reading and writing procedures mediated by cordel literature, in Youth and Adult Education, in a state school in the city of Alagoa Grande. It is an action research, with qualitative analysis of the data and development of an intervention proposal. Among the reasons that triggered interest in this study we highlight the difficulty in finding suitable didactic material, as well as forming adult classes for literacy / literacy. In this sense, the school for students outside the age group of Regular Education should be thought in a different way, with a content approach and methodological proposals developed to promote learning, since these people bring life experiences and knowledge even if not systematized . Illiteracy is ignorance of the techniques used in writing and non-literacy is the lack of familiarity with the written world, so this study is justified by the contribution that will be given to the students and teachers of the Network of Youth and Adult Literacy of the Paraíba, in order to help and improve reading and writing practices, focusing on the importance of writing and reading to the society in which we live. The theoretical contributions that underlie the research are the studies about literacy in the perspective of literacy, in which writing and reading depart from everyday elements to become meaningful practices. This study is based on classical theorists such as Brandão (1984), Freire (1975), Oliveira (2001), Rego (2001), Cosson (2009), Kleiman (2010), among others, situating young people and adults in literacy and literacy.